Re(de)fining address: an overlooked French phenomenon (2004)
In this paper I examine the origins and history of the modern French use of the definite article in address phrases (e.g. "Bonjour, la classe"), a usage which contrasts very strongly with, for example, the ungrammaticality of the definite article in address in English. I show that the key to understanding the development is a period during which the presence of the article appears to be triggered by the presence of a restrictive modifier within the phrase, and I provide evidence for this from old French texts. I further suggest that this is the result of a reanalysis of an earlier state of affairs for which I provide evidence of the Latin etymon of the French definite article, ille, present in phrases for that same reason but phrases which were not, strictly speaking, addresses. The developments since the old French period are then discussed together with some detailed consideration of the influence of developments within the first-person possessives. I consider briefly some allegedly parallel patterns found in Italian and Romanian, and conclude that these are not straightforwardly descended from the same Latin patterns. However, the approach adopted for French may work for these as independent innovations within Italian and Romanian respectively. Finally I consider the extent to which the use of the definite article in address is impossible in English and raise questions about the extent to which such patterns are syntactically or pragmatically conditioned.